2020
DOI: 10.1212/wnl.0000000000010929
|View full text |Cite
|
Sign up to set email alerts
|

Head injury and neuropsychiatric sequelae in asylum seekers

Abstract: ImportanceAsylum seekers experience a high burden of physical and psychological trauma, yet there is a scarcity of literature regarding the epidemiology and sequelae of head injury (HI) in asylum seekers.ObjectiveTo examine HI prevalence and association with neuropsychiatric comorbidities in asylum seekers.MethodsA retrospective cross-sectional study was performed through review of 139 medical affidavits from an affidavit database. Affidavits written from 2010 to 2018 were included. Demographic and case-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…In our study, severe headache was more common among those who experienced head injury with loss of consciousness. A study of asylum seekers in the US showed that almost half (42.5%) reported a history of head injury, which is similar to our finding of 40.2% for HSCL (39).…”
Section: Severe Headache Comorbid With Ptsdsupporting
confidence: 89%
“…In our study, severe headache was more common among those who experienced head injury with loss of consciousness. A study of asylum seekers in the US showed that almost half (42.5%) reported a history of head injury, which is similar to our finding of 40.2% for HSCL (39).…”
Section: Severe Headache Comorbid With Ptsdsupporting
confidence: 89%
“…Another recent study of U.S. asylum-seekers found a higher prevalence of head injury than in our sample, in addition to clients with head trauma more likely to have depression. Differences from our study could be potentially explained by sample composition, differences in clinician background, and inconsistent use of validated instruments leading to an underestimate of PLOS ONE head trauma which we outline as limitations [33]. Further, we did not capture acquired head injury from strangulation in our sample, which future studies could consider prospectively evaluating for since this type of head injury can occur above and beyond traumatic head injury and incur neurocognitive sequelae as well.…”
Section: Discussionmentioning
confidence: 94%
“…Head trauma was comorbid with a range of physical and mental health conditions, although more studies documented mental health comorbidities (n = 12, 55%) than physical ones (n = 9, 41%). Among mental health conditions, depression (n = 9) 13,16,17,25,27,28,30,31,33 and PTSD (n = 9) 13,16,17,19,26,27,31,33,34 were cited most frequently, followed by anxiety disorder (n = 4) 25,27,30,34 and suicidal ideation (n = 4). 25,26,28,30 Physical health conditions cited included the following: headaches (n = 6), 18,24,25,27,28,30 dizziness (n = 3), 25,28,30 sleep disturbance (n = 2), 18,34 impaired memory (n = 2), spinal injuries (n = 2), 24,34 and chronic pain (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The most documented mechanism of injury was direct impact or head strike through a beating or blow against the head (n = 9, 41%). 13,18,20,[25][26][27][28][29][30] Three additional studies reported that blunt trauma was the leading mechanism of head trauma in their sample but did not specify the percentage that this represented. 16,19,31 Two studies cited blast-induced head trauma as the predominant mechanism of injury in their study population.…”
Section: Head Trauma Characteristicsmentioning
confidence: 99%